2005
DOI: 10.1111/j.1463-1318.2005.00901.x
|View full text |Cite
|
Sign up to set email alerts
|

Patients' expectations of colorectal surgery for cancer

Abstract: Age, gender and education influence the pre-operative expectations of patients undergoing surgery for colorectal cancer. In addition to the surgical standard, the care of the individual patient must be given due consideration in the treatment strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 12 publications
(13 reference statements)
0
16
0
Order By: Relevance
“…Likewise, a recent 10‐year longitudinal study of HRQoL among German colorectal cancer survivors found that survivors reported poorer HRQoL for most measures compared with controls, with disparities in HRQoL worsening over time . Persistent or worsening disparities in HRQoL between short and long‐term colorectal cancer survivors may be due to the unmet continuation of bothersome symptoms and effects such as constipation, diarrhea, pain, fatigue, and dyspnea, and unmet expectations for improvements in treatment‐related outcomes over time . Colorectal cancer patients are often treated with surgical proctectomy resulting in a temporary ostomy.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, a recent 10‐year longitudinal study of HRQoL among German colorectal cancer survivors found that survivors reported poorer HRQoL for most measures compared with controls, with disparities in HRQoL worsening over time . Persistent or worsening disparities in HRQoL between short and long‐term colorectal cancer survivors may be due to the unmet continuation of bothersome symptoms and effects such as constipation, diarrhea, pain, fatigue, and dyspnea, and unmet expectations for improvements in treatment‐related outcomes over time . Colorectal cancer patients are often treated with surgical proctectomy resulting in a temporary ostomy.…”
Section: Discussionmentioning
confidence: 99%
“…Holzer et al evaluated the relationship between the preoperative expectations in patients with colorectal cancer and their age, gender, and socioeconomic status [10]. These authors learned that complete cure of the disease was the prime expectation of the patients (95%).…”
Section: Patient Satisfactionmentioning
confidence: 98%
“…This demonstrates the importance of QoL to patients following treatment for colorectal malignancy. Stomas are generally perceived poorly by preop-erative patients and individuals in the general population [1], but it is noteworthy that no significant QoL score differences were found between patients with a stoma compared with patients with a low colorectal anastomosis [2], although there may be a degree of patient self-selection in this decision. Conversely, patients were prepared to tolerate the side effects of adjuvant treatment for small improvements in overall survival.…”
Section: Discussionmentioning
confidence: 98%